Studi Kasus Program CSR PT. Pertamina RU II Sungai Pakning pada Program Revitalisasi Kawasan Mangrove di Provinsi Riau - Asri Dewi; Yeni Rosilawati (CHANNEL: Jurnal Komunikasi, 2020)
The company's contribution to building society is implemented through the Corporate Social Responsibility program, known as the CSR program.  The concept of CSR is influenced by the idea that the existence of a company depends on the life of the environment and the community in which it lives and is adjusted to the problems that exist around the company's location as a form of responsibility to the stakeholders and the surrounding environment.  This study aims to describe the implementation of an environmental conservation-based CSR program carried out by PT Pertamina RU II Sungai Pakning.  This study uses a qualitative paradigm while the data in this study were collected through in-depth interviews with local communities, local community leaders, CDOs, and CSR coordinators who are directly responsible for CSR programs.  Besides, the secondary data was obtained through the company’s website, CSR reports, and news in the mass media about the CSR of PT Pertamina RU II Pakning. The results of this study indicate that the environmental-based CSR program is implemented through a mangrove conservation and revitalization program through community empowerment. Local people are actively involved in handling environmental issues through working groups on conservation and revitalization of mangrove areas, cultivation of brackish fish, and product processing.